Long term electricity storage by oxygen liquefaction and LNG oxy-combustion. (April 2020) - Barsali, Stefano; Ciambellotti, Alessio; Fioriti, Davide; Giglioli, Romano; Paganucci, Fabrizio; Pasini, Gianluca
Highlights: Innovative scheme exploiting oxygen liquefaction as a means for storing excess electricity generation from renewable sources. Stored energy is used through an oxycombustion system with LNG. Equivalent round trip efficiency even higher than 100% are reached if compared with analogous functions performed with state of the art gas turbines. Carbon dioxide is captured in liquid phase as a by-product of the system. Abstract: The paper proposes an innovative scheme exploiting oxygen liquefaction as a means for storing excess electricity generation from renewable sources. Liquid oxygen is then used in an oxy-combustion process with LNG to generate electricity when renewable energy generation is below the demand. An equivalent round trip efficiency is defined to make it possible comparing the system performances with hybrid plants including conventional generation and storage. The proposed scheme exhibits very high equivalent round trip efficiency, giving the system operators the opportunity to integrate more and more renewable energy generation inside power systems. Liquefied carbon dioxide and water are byproducts of the process. The size of the plant and of the storage tanks needed for a 4 TWh yearly demand with a peak around 800 MW is compatible with state-of-the-art systems used for LNG storage in similar size gas power plants.